The Impact of Kahoot as Learning Evaluation on Students' Motivation in Learning English at Senior High School - Salsabila, Rahma; Apoko, Tri Wintolo (Universitas Pahlawan Tuanku Tambusai, 2024)
The use of Kahoot as a learning evaluation tool has been effective in increasing students' learning motivation. This study aimed to investigate in depth the impact of using the platform as an evaluation tool on students' motivation to learn English at the senior high school level. The study employed a mixed methods approach to comprehensively understand how the use of the platform affects the motivation of students in learning English. The data was collected through semi-structured interviews with a subset of five students in grade 11 who had been experiencing and using Kahoot as an evaluation tool in English language lessons. The results revealed that the participants generally perceived Kahoot to be a valuable resource for enhancing English classes, enabling students to learn and practice subjects, assess their understanding, and receive feedback to enhance their performance. Specifically, the highest mean score of 3.78 (SD = .702) was observed, showing Kahoot could enhance English language learning process, and the mean score was 3.71 (SD= .729), indicating a generally positive perception. Moreover, the finding of this study showed that students generally perceived the Kahoot platform to be an accessible and easy-to-use tool for English classes. In addition, it was found that participants generally believed Kahoot as an effective tool for fostering their English learning process and motivated them to learn.